後疫情時代臺灣中部地區國小教師線上教學滿意度影響因素之探討 Factors Influencing Elementary Teachers' Satisfaction With Online Teaching in the Postpandemic Era in Central Taiwan - 夏榕文 Jung-Wen Hsia (National Taiwan Normal University, 2024)
2019年底新冠病毒（COVID-19）在全球開始散播，各處均傳出疫情，直到2021年5月疫情嚴重時期，臺灣各級學校紛紛改為線上上課，此後，各校又根據疫情轉變，滾動式調整教師以實體或線上方式教學。基於國小教育是各級教育的重要基礎，而國小教師在疫情期間面對教學方式的改變尤為劇烈，且線上教學未來可能成為常用的教學方法，因此探討影響後疫情時代國小教師線上教學滿意度的因素甚具研究價值。本研究意欲建構一個影響國小教師線上教學滿意度之理論模式，此模式整合學生因素（學生學習投入）、教師因素（教學效能、教學樂趣及訓練充分性）及技術因素（知覺易用性），共同探討此三大因素對國小教師線上教學滿意度之影響。本研究採用分層與便利抽樣，對任教於臺灣中部地區（臺中市、南投縣及彰 化縣）之國小且具有線上教學經驗的教師發放問卷，最後回收250份有效問卷，以偏最小平方法分析資料。研究結果顯示，學生學習投入、教學效能、教學樂趣及訓練充分性均正向顯著影響國小教師線上教學滿意度，但知覺易用性對教師線上教學滿意度沒有影響，本研究最後提出實務意涵及未來研究建議。 Research Motivation and Objectives The global outbreak of the new coronavirus (COVID-19) in late 2019 led to a widespread pandemic. When the pandemic became most intense in Taiwan, schools at all levels were required to shift to online teaching, with such instruction continuing until May 2021. After this period Taiwanese schools adjusted their teaching methods, with many schools alternating between in-person and online instruction on the basis of the evolving pandemic conditions. The sudden transformation in teaching methods considerably affected teachers at all levels of education. Nevertheless, research investigating teachers' satisfaction with online instruction has primarily focused on university or high school teachers. However, elementary education serves as a crucial foundation for all levels of education. Compared with university teachers, elementary school teachers are less familiar with online teaching and face challenges in effectively conducting online classes. Furthermore, online teaching in elementary schools may become a common instructional method in the future. Therefore, investigating methods to enhance the satisfaction of elementary school teachers with online teaching is imperative. This study identified the factors influencing elementary school teachers' satisfaction with online teaching. Literature Review On the basis of a review of the literature, this study divided the factors influencing elementary school teachers' satisfaction with online teaching into three categories: student-related, teacher-related, and technology-related factors. Regarding student-related factors, this study used student engagement as a predictive variable for analyzing teacher satisfaction with online teaching. Regarding teacher-related factors, teaching efficacy, teaching enjoyment, and training adequacy were included as predictive variables. Regarding technology factors, perceived ease of use was employed as a predictive variable. These factors were used to establish a theoretical model for elucidating the factors influencing elementary school teachers' satisfaction with online teaching. Methods This study employed stratified sampling and convenience sampling. Questionnaires were distributed to elementary school teachers in central Taiwan (Taichung City, Nantou County, and Changhua County) who had experience in online teaching. Descriptive statistical analysis was conducted using SPSS. Furthermore, the partial least squares (PLS) method, which has been demonstrated to be suitable for exploratory research and theory development, was employed in this study. Because studies that have constructed a theoretical model for elementary school teachers' online teaching satisfaction are limited, this study considered PLS to be appropriate for developing such a model. Consequently, the hypotheses of this study were tested using PLS, which was employed to assess both the measurement model and the structural model. Results Of the 250 valid samples that were collected, 93 (37.2%) were from male teachers and 157 (62.8%) were from female teachers. Regarding age, the majority of the teachers (129 individuals) were aged 31-40 years, accounting for 51.6% of the sample, followed by those (65 individuals) aged 41-50 years, accounting for 26.0% of the sample. In terms of teaching location, 139 teachers (55.6%) were from Taichung City, 69 (27.6%) were from Changhua County, and 42 (16.8%) were from Nantou County. In terms of teaching experience, the majority of the teachers (98 individuals) had 6-10 years of experience, accounting for 39.2% of the sample, followed by those (65 individuals) with 11-15 years of experience, accounting for 26.0% of the sample. Moreover, the majority of the teachers (103 individuals, 41.2% of the sample) had experience in online teaching of 6 months to 1 year. Furthermore, most teachers (171 individuals, 68.4% of the sample) held a university degree. An analysis of the measurement model indicated that all six variables used in this study had sufficient reliability and construct validity. The results of the structural model analysis revealed that student engagement, teaching efficacy, teaching enjoyment, and training adequacy significantly and positively influenced the elementary school teachers' satisfaction with online teaching. However, perceived ease of use did not significantly influence the teachers' satisfaction with online teaching. Discussion and Implications Online teaching and traditional teaching differ in their contexts. Therefore, future research seeking to further explore the impact of specific predictive variables, such as student engagement and teaching efficacy, on satisfaction with online teaching should complete observations of and interviews with elementary school teachers with respect to their experiences in online teaching. This approach can contribute to a more comprehensive understanding of the factors influencing teachers' satisfaction with online teaching and the causal relationships among them. In addition, although the elementary school teachers were unfamiliar with online teaching platforms prior to the pandemic, they were likely regularly exposed to various technological platforms, such as learning management systems and social media, before engaging in online teaching. This may explain why the teachers' satisfaction with online teaching was not affected by the ease of platform use. Nevertheless, platforms that emphasize interactions and discussions may contribute to enhanced teaching efficacy and student engagement. Additionally, incorporating features such as mini-games into a teaching platform may increase teaching enjoyment and student engagement. Such adjustments may influence the satisfaction of elementary school teachers with online teaching. On the basis of the study findings, this study provides several practical recommendations. First, the study recommends enhancing student engagement in online teaching and learning by incorporating engaging digital teaching resources, implementing effective teaching strategies, and enhancing the interactive features on teaching platforms to increase student engagement. Second, the study recommends enhancing teachers' online teaching efficacy. This can be achieved by providing technical support specifically tailored to the needs of elementary school teachers engaged in online teaching. Moreover, encouraging these teachers to participate in professional learning communities can help address problems related to online teaching. Third, this study recommends increasing teachers' online teaching enjoyment by, for example, introducing more engaging games or competitions on online platforms and establishing professional learning communities in which teachers can share teaching software and resources. Finally, this study recommends enhancing the adequacy of training for online teaching. Schools are encouraged to offer both synchronous and asynchronous online teaching training courses that cover various aspects such as online teaching techniques, online classroom management, and psychological adjustment.